Nicotine normalizes cortico-striatal connectivity in non-smoking individuals with major depressive disorder. (November 2018) - Janes, Amy; Zegel, Maya; Ohashi, Kyoko; Betts, Jennifer; Molokotos, Elena; Olson, David; Moran, Lauren; Pizzagalli, Diego
Abstract Nicotine dependence and major depressive disorder (MDD) are highly comorbid, yet causal links between these prevalent disorders are unclear. One possible mechanism is that nicotine ameliorates MDD-related neurobiological dysfunction in specific networks. For instance, cortico-striatal circuitry is enhanced by nicotine, and such paths are disrupted in individuals with MDD. Specifically, MDD has been associated with reduced connectivity between the nucleus accumbens (NAc) and rostral anterior cingulate cortex (rACC) but enhanced connectivity between the dorsal striatum (DS) and dorsolateral prefrontal cortex (DLPFC). Determining whether nicotine normalizes these circuits in non-smokers with MDD may elucidate mechanisms underlying links between disorders. This was tested by administering placebo and a 2-mg dose of nicotine to unmedicated non-smokers with and without MDD prior to collecting resting-state functional magnetic imaging data using a cross-over design. On placebo, individuals with MDD showed significantly reduced NAc–rACC and a trend for enhanced DS–DLPFC functional connectivity relative to healthy controls. In MDD, acute nicotine administration normalized both pathways to the level of healthy controls, while having no impact on healthy controls. Nicotine's effects on NAc–rACC connectivity was influenced by anhedonia, consistent with the role of this network in reward and nicotine's ability to enhance reward deficiencies in MDD. These results indicate that nicotine normalizes dysfunctional cortico-striatal communication in unmedicated non-smokers with MDD. Nicotine's influence on these circuitries highlights a possible mechanism whereby individuals with MDD are more vulnerable to develop nicotine dependence. Findings suggest that nicotinic agents may have therapeutic effects on disrupted cortico-striatal connectivity.